Habitar casas com móveis fixos: do projeto ao contemporâneo - Garcia, Bárbara Cardoso (2019)
This research is focused on the study of built-in furniture, made of masonry or reinforced concrete, integrated to the architectural design of modern residences in São Paulo from the 1960’s and 1970’s. The aim of the research was to observe and understand the design issues and the domestic sociability motivated by the built-in furniture, of these single-family dwellings, how this type of furniture was appropriated by their inhabitants, how it was commented on by professional journals and lifestyle magazines and how it was considered in the criticism and historiography of architecture and design.